Catalyst-dependent morphological evolution by interfacial stress in crystalline-amorphous core-shell germanium nanowires - Palavalli, N.D.; Yaghoubi, A.; Lai, C.C.; Tin, C.C.; Javey, A.; Chueh, Y.L. (Royal Society of Chemistry, 2015)
Directing the morphological evolution of one-dimensional materials in order to tune their properties for a variety of practical applications in optical sensing and solar cells is an ongoing effort. Here, we establish a systematic method for exerting control over the morphology of nanowires (NWs) grown via a vapour-solid-solid (VSS) process from different metal catalysts. We use germanium, a technologically important material, to demonstrate how catalysts influence the axial growth rate of a crystalline core against the lateral vapour deposition of an amorphous shell which in turn deforms the NWs into straight, tapered or spiral geometries due to interfacial stress. Finite element method (FEM) and molecular dynamic (MD) simulations are further utilized to confirm the proposed mechanism of deformation in crystalline-amorphous core-shell NWs.